An evaluation of e-learning in arabic language learning / M.Khalid Awang …[et al.] - Awang, M.Khalid; A. Rahman, M.Nordin; A. Sanny, Syarilla; Ghazali, M.H. (2004)
The purpose of this research is to evaluate the effectiveness of e-leaming in Arabic language learning. Since the Arabic language is considered as one of the major language throughout the world, it is crucial to find an alternative way to support and help people in Arabic language learning. The electronic learning which is known as e-leaming is considered as one of the most effective and interesting method of learning in this information age. In this research, the integration of Internet technology, multimedia technology and game has been implemented as one of the e-learning approach. A simple web based Arabic game is developed to evaluate the effectiveness of the e-learning in Arabic language learning. A group of students have been selected and participated in the evaluation. The research has shown that the e-leaming approach is suitable and very helpful in Arabic language learning. The e-leaming also can be considered as one of the alternative way in Arabic language learning.